Antibacterial adhesive self-healing hydrogels to promote diabetic wound healing. (1st July 2022) - Chen, Jueying; He, Jiahui; Yang, Yutong; Qiao, Lipeng; Hu, Juan; Zhang, Jie; Guo, Baolin
Abstract: The development of compressible, stretchable and self-healing hydrogel dressings with good adhesive, antibacterial and angiogenesis properties is needed to promote the regeneration of diabetic wounds in clinical applications. In this work, a series of self-healing, adhesive and antibacterial hydrogels based on gelatin methacrylate (GelMA), adenine acrylate (AA), and CuCl2 were designed through covalent bonding, coordination complexation of Cu 2+ and carboxyl groups and hydrogen bonding to promote diabetic wound healing. These hydrogels exhibit efficient self-healing properties, remarkable fatigue resistance, and good adhesive properties due to the hydrogen bond and the metal-ligand coordination provided by the Cu 2+ and the carboxyl group. The GelMA/AA/Cu1.0 hydrogel (containing 1.0 mg/mL Cu 2+ ) with well-balanced biocompatibility and antibacterial properties exhibited efficient hemostatic performance in a mouse liver trauma model and significantly promoted the healing process in a full-thickness skin diabetic wound model. The immunohistochemistry results showed that the GelMA/AA/Cu1.0 hydrogel can promote regular epithelialization and collagen deposition when compared to the Tegaderm TM Film, GelMA hydrogel, and GelMA/AA/Cu0 hydrogel. The immunofluorescence results confirmed that the GelMA/AA/Cu1.0 hydrogel can reduce the expression of proinflammatory factors and promote angiogenesis. In conclusion, the GelMA/AA/Cu hydrogel is an effective wound dressing to promote the healing process of diabetic skin wounds. Statement of significance: Diabetic wounds exhibit an extremely high risk of bacterial infection and poor angiogenesis in a high-sugar environment, hindering their healing process. Hydrogel wound dressings are a promising wound care material that need to have stable and long-lasting adhesive properties, avoid shedding, provide lasting protection to wounds, antibacterial properties and promote angiogenesis. In this study, a series of self-healing, adhesive, and antibacterial hydrogels based on gelatin methacrylate (GelMA), acrylated adenine (AA), and CuCl2 were designed and synthesized via free radical polymerization, hydrogen bond, and ionic bond to promote diabetic wound healing. Overall, GelMA/AA/Cu hydrogels are promising materials to promote diabetic wound healing. Graphical abstract: Image, graphical abstract